Respuesta :

Answer:

(3x + 1)(2x - 3)

Step-by-step explanation:

Given

6x² - 7x - 3

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term

product = 6 × - 3 = - 18 and sum = - 7

The factors are + 2 and - 9

Use these factors to split the x- term

6x² + 2x - 9x - 3 ( factor the first/second and third/fourth terms )

= 2x(3x + 1) - 3(3x + 1) ← factor out (3x + 1) from each term

= (3x + 1)(2x - 3) ← in factored form

Answer:

(2x−3)(3x+1)

You factor by finding the greastest common factor (gcf)